Controlled positioning of nanoparticles on a micrometer scale - Enderle, Fabian; Dubbers, Oliver; Plettl, Alfred; Ziemann, Paul (Beilstein Journal of Nanotechnology, 2012)
For many applications it is desirable to have nanoparticles positioned on top of a given substrate well separated from each other and arranged in arrays of a certain geometry. For this purpose, a method is introduced combining the bottom-up self-organization of precursor-loaded micelles providing Au nanoparticles (NPs), with top-down electron-beam lithography. As an example, 13 nm Au NPs are arranged in a square array with interparticle distances >1 µm on top of Si substrates. By using these NPs as masks for a subsequent reactive ion etching, the square pattern is transferred into Si as a corresponding array of nanopillars.
Keywords: electron beam lithography; nanoparticles; positioning; self-assembling; unconventional lithography